Pengaruh Metode Directed Reading Activity Berbantuan Media Genially Terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas IV - Nengsi, Yosa Pitria; Agusdianita, Neza (Universitas Bengkulu, 2026)
This study aims to determine the effect of using the Directed Reading Activity (DRA) method assisted by Genially interactive media on the learning outcomes of Indonesian language of fourth grade students of SDN Gugus 19 Bengkulu City. The type of research is quantitative research with Quasi Experimental method and research design The Matching Only Pretest-Posttest Control Group Design. The population in this study were fourth grade students of SDN Gugus 19 Bengkulu City with the criteria of elementary schools with public status accredited B, using the independent curriculum. The research sample consisted of fourth grade students of SDN 71 Bengkulu City as the experimental group and SDN 69 Bengkulu City as the control group. Data was collected through pretest and posttest tests in the form of multiple choice questions. The results of the independent smple t-test test showed the tcount value = 3.376 and the sig. (2-tailed) value is 0.001 and the ttable distribution value is 2.012. So that the value of tcount> ttable (3.376> 2.012) and sig. (2-tailed) of 0.001 <0.05. The data shows that Ha is accepted, which means that there is an influence on the average learning outcomes in the experimental group of 81.30 and the control group of 67.69 due to differences in treatment in the two groups, namely the experimental group using the DRA method assisted by Genially Interactive Media and in the control group not using the DRA method assisted by Genially Interactive Media. Thus, it can be concluded that the Directed Reading Activity method assisted by Genially interactive media has an effect on the learning outcomes of fourth grade students of SDN Gugus 19 Bengkulu City.